Analisis Faktor yang Berpengaruh terhadap Tingkat Kelulusan UKDI Dokter Baru Lulusan Fakultas Kedokteran Universitas Airlangga - Budi Utomo; Roostantia Roostantia; Indri Safitri (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: The average passing rate of Airlangga University School of Medicine (accredited A) graduates on the Indonesian Doctor Competence Examinations (UKDI) from Batches 1 to 17 was in the range of 90-95%, which was above the national average. The achievement, however, has declined to approximately 80-85% in Batch 23 - the last UKDI. These school’s new graduates are the product of a series of educational processes within the faculty of medicine: input in the form of student selection, educational process incorporating: educational programs, academic staff, educational resources, learning outcomes assessments, evaluation of educational programs and continuous updates, and the output which are medical doctors passing the UKDI. This study aims at exploring the factors that influence the success of newly graduated doctors to pass the UKDI. The results were expected to be used as considerations for the improvements of materials and teaching methods which referring to the National Competencies for Physician (SKDI).Method: The study was divided into two stages. Observational study design was implemented on the first stage. Second, the analytical observational cross-sectional study design was applied. The unit of analysis was derived from secondary data, a collection of documents of students studying in the School of Medicine Airlangga University and of the UKDI test scores.Results: The analysis results showed that the variable most affecting the passing of UKDI in this study was the GPA at the bachelor stage (OR = 67.44; p=0.001). The mathematical model of the logistic regression is: y = constant + a1x1 + a2x2 +..... + anxn, being y = -8.83 + 67.44 (GPA bachelor). The probability (p) of passing a new doctor of the school on the UKDI examination can be predicted using the formula: p = 1 / (1 + e-y), with e = 2.7 (natural number).Conclusion: The variable most affecting the passing of UKDI in this study was the GPA at the bachelor stage (OR = 67.44; p=0.001).